On the Dynamics of Disequilibrium: A Simple Remark - Laroque, Guy (Review of Economic Studies, 1978)
Journal Article On the Dynamics of Disequilibrium: A Simple Remark Get access Guy Laroque Guy Laroque Insee, Paris Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 273–278, https://doi.org/10.2307/2297342 Published: 01 June 1978 Article history Received: 01 November 1975 Accepted: 01 March 1977 Published: 01 June 1978